Colonial Society And Taxation - Tord, Javier (1977)
The "Hacienda Real" was one of the four major forms of political control that Spain had on its American colonies. "All you accustom to write in many letters - tells the King to the Audiencia of Charcas in 1595 - you will reduce to four different issues: Government, Justice, War and Finance" In the framework imposed on them by the colonial system, lawyers and officials dealt with great contemporary relevance of the themes of the Royal Treasury Indiana.